(untitled) (Journal of Libya for geographical studies, 2024)
The semi-playa flat (Alssd) is considered one of the important plain areas in the Tobruk region, It is one of the largest flat areas in it. And it is characterized by a semi-flat surface, and it consists of fine-grained sediments, with horizontal stratification, representing the remnants of the sediments of closed fresh water bodies (ponds and lakes) that were formed during previous periods of time during which climatic conditions prevailed. More moisture than the current conditions. Its area is 95.5 square kilometers, That is, about 15% of the area of the Tobruk region, which has an area of 648 km2. Its surface slopes towards the west and northwest, from an altitude of 90 m south of the Al-Marsas area to 10 m south of the Ain Al-Ghazala area in the west, with a slope rate of 23%. Limestone rocks formed the basis of 69.67% of the study area, which are Tertiary formations. While the components of the fourth time constituted 30.33% of the study area, represented by river sediments, beach sediments, and Sebkha sediments. It seems that the surface of the semi-playa (Alssd) was linked in its origin and development to the coastal conditions and geological events that the study area experienced, as it formed between two parallel fractures along with many breaks and cracks, as the surface took the shape of a rectangle, and it is linked to areas of structural weakness in the study area. It is likely that the sediments of Alssd surface were created as a result of the accumulation of fine sediments of silt, calcareous mud and fine sand in the form of thin stratified horizontal layers. These sediments accumulated in a fresh water medium represented in many ponds and lakes that prevailed during the fourth time (Pleistocene and Holocene), and it seems that the surface sediments of the flat, according to previous studies, ranged between 125-150 thousand years ago. The average sizes of surface sediments among gravel amounted to 4.06% of the total samples, the average percentage of sand of different sizes reached 82.65%, and the average percentage of coarse and medium silt reached 13.29%.